Differences in knee joint degeneration between primary hip osteoarthritis and hip osteoarthritis secondary to hip developmental dysplasia: A propensity score-based analysis. Issue 6 (2nd November 2021) - Sato, Ryuichi; Ando, Wataru; Hamada, Hidetoshi; Takao, Masaki; Saito, Mitsuru; Sugano, Nobuhiko
Abstract: Objectives: This study aimed to investigate differences in lower limb alignment and the prevalence of knee osteoarthritis (OA) among patients with primary hip osteoarthritis (PHOA) versus those with hip osteoarthritis secondary to developmental dysplasia of the hip (DDH-OA). Methods: We compared 83 patients who underwent primary total hip arthroplasty for unilateral PHOA or DDH-OA after performing propensity score matching. The prevalence of knee OA and lower limb alignment were evaluated on preoperative plain radiographs. Results: The prevalence of knee OA on the ipsilateral side was significantly higher in the PHOA group than in the DDH-OA group ( p =.019), whereas there was no difference between the groups on the contralateral side ( p = .631). Lower-limb alignment was more valgus on the ipsilateral side in the DDH-OA group than the PHOA group, whereas it was not significantly different on the contralateral side between groups. Conclusion: The prevalence of knee OA and lower-limb malalignment on the ipsilateral side of hip OA were different for PHOA and DDH-OA patients. Shifting the mechanical axis of lower limbs might be associated with the prevalence of knee OA and lower limb malalignment in the presence of unilateral hip OA.